Refining tourist’s place experience through placemaking: concepts and correlations - Zakariya, Khalilah; Mohyuddin, Amira; Mohd. Yaman, Maheran (Common Ground Publishing Pty Ltd, 2007)
Experiencing places is an integral process in tourism. The outcome of the experience will either have a longlasting impact on the tourists or just merely a short-term impression of the place visited. Studies on tourist experience have been widely discussed to better understand the diverse processes and variables involved in creating a positive tourist experience.Place experience is closely related to both fields of landscape architecture and tourism planning. Spaces created become places, and places act as the setting where tourists interact with the people and experience the environment of the destination visited. Experiences are undoubtedly different from one tourist to another as each tourist brings with them diverse backgrounds, conceptions and expectations. Therefore, as designers and planners of places, it is vital to understand what makes a great destination in order to give a high quality of experience to tourists. Placemaking and creating sense of place are noted by various literatures as being important in building and strengthening an identity for the attraction. The concepts of place, place experience, tourist experience and placemaking will be further discussed in this paper. It will subsequently talk about the correlation among these concepts in relation to refining tourist’s place experience. Place characters that have significant roles in creating a more refined place experience have also been identified. In creating places for tourism, it is essential to focus on the characteristics of the place that appeal to the tourists, as the atmosphere created will influence the value of experience gained by the tourists. A pilot study on the Middle Eastern